MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN ALAM MATERI MENGIDENTIFIKASI CARA TUMBUHAN HIJAU MEMBUAT MAKANAN MELALUI MODEL PICTURE AND PICTURE PADA SISWA KELAS V SEMESTER I SEKOLAH DASAR NEGERI 03 KALING KECAMATAN TASIKMADU KABUPATEN KARANGANYAR TAHUN PELAJARAN 2015/2016 - Sumardi, - (Widya Wacana: Jurnal Ilmiah, 2015)
The main problem of this research is whether improving the study result of Science aboutidentifying the way greenery makes its own food to the fifith grade students in SDN 03 KalingTasikmadu Karanganyar in the acdemic year of 2015/2016 can be done by using the picture andpicture model. The purpose of this research is to improve the study result of Science aboutidentifying the way greenery makes its own food through picture and picture model. Thisresearch is in the form of Classroom Action Reasearch which is carried out in SDN 03 KalingTasikmadu Karangnayar in the academic year of 2015/2016. The subject of the reseacrh is thefifth grade students that consists of 23 students.The research was carried out for 3 months, strated from August 2015 until October 2015.The data resource and data in this research is the students’ test result and the document. Thedata collecting method used in this research is observation and document analysis. The result ofthe research shows a significant improvement in the students’ Science study result aboutidentifying the way greenery maks its own food. In the pre research, the students’ score is 65,22.While in cycle I is 73,04, 78,70 in cycle II, and 85,65 in cycle III. Therefore, it can be concludedthat picture and picture model can improve the study result of Science about identifying the waygreenery makes its own food to the fifith grade students in SDN 03 Kaling TasikmaduKaranganyar in the acdemic year of 2015/2016.key words: Study result, picture and picture model, Science.